Chlorination Disinfection By-products and Pancreatic Cancer Risk - Do, Minh T. (National Institute of Environmental Health Sciences, 2005)
Chlorination disinfection by-products (CDBPs) are produced during the treatment of water with chlorine to remove bacterial contamination. CDBPs have been associated with an increased risk of bladder cancer. There is also some evidence that they may increase the risk of pancreatic cancer. We report results from a population-based case–control study of 486 incident cases of pancreatic cancer and 3,596 age- and sex-matched controls. Exposure to chlorination by-products was estimated by linking lifetime residential histories to two different databases containing information on CDBP levels in municipal water supplies. Logistic regression analysis found no evidence of increased pancreatic cancer risk at higher CDBP concentrations (all odds ratios < 1.3). Null findings were also obtained assuming a latency period for pancreatic cancer induction of 3, 8, or 13 years.